KAJIAN SOSIOLOGI SASTRA PADA NOVEL EDELWEIS TAK SELAMANYA ABADI KARYA LIAIKO DAN RELEVANSINYA DALAM PEMBELAJARAN SASTRA DI SEKOLAH MENENGAH ATAS (SMA) - Puput Fuzi Wulandari (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to describe: (1) Describe the social setting of the author of the Edelweis Tak Selamanya Abadi novel by Liaiko. (2) Describe the social setting of the community contained in Liaiko's Edelweis Tak Selamanya Abadi novel. (3) Describe the response of readers of Liaiko's Edelweis Tak Selamanya Abadi novel. (4) Describe the relevance of research results in literary learning in high schools (SMA). The method used in this study is a descriptive qualitative method with the Sociology of Literature approach. The research data source is the Edelweis novel, which is not forever eternal, the work of Liaiko. The main data in the research are novel texts. Data collection techniques using reading techniques, note taking techniques and interviews. Researchers play a direct role as the main instrument of research. Data validation was obtained through method triangulation and source triangulation and theory triangulation. Data analysis used by the research is a flow analysis model by collecting data, reducing data, presenting data, and verifying data. The results obtained from the study showed that: (1) the author's social setting such as the author's life history and the social background of the author's family had an influence on the creation of Edelweis novel Not Forever Abadi Karya Liaiko (2) the social background contained in Edelweis's novel is Never Forever Abadi Karya Liaiko relates to the reality that exists in the real world, such as sacrifice, romance and the background and point of view of the author (3) the response of expert and general readers who say that the Edelweis novel is Not Forever Lasting Liaiko's work states that the excellence of this novel lies in the author's point or point of view (4) the relevance to literary learning in high school is found in the K13 curriculum learning the novel reading material on KI 3 and KD 3.4 reviews the contents and linguistic elements of a novel and KD 4.4 presents a review of the content and linguistic elements of a novel in surgical activities book. Keywords: Novels, Sociology of Literature, Literature Learning.